Therapeutic Cancer Vaccine and Combinations With Antiangiogenic Therapies and Immune Checkpoint Blockade - Mougel, Alice; Terme, Magali; Tanchot, Corinne (Frontiers in Immunology, 2019)
Considering the high importance of immune surveillance and immune escape in the evolution of cancer, the development of immunotherapeutic strategies has become a major field of research in recent decades. The considerable therapeutic breakthrough observed when targeting inhibitory immune checkpoint molecules has highlighted the need to find approaches enabling the induction and proper activation of an immune response against cancer. In this context, therapeutic vaccination, which can induce a specific immune response against tumor antigens, is an important approach to consider. However, this strategy has its advantages and limits. Considering its low clinical efficacy, approaches combining therapeutic cancer vaccine strategies with other immunotherapies or targeted therapies have been emphasized. This review will list different cancer vaccines, with an emphasis on their targets. We highlight the results and limits of vaccine strategies and then describe strategies that combine therapeutic vaccines and antiangiogenic therapies or immune checkpoint blockade. Antiangiogenic therapies and immune checkpoint blockade are of proven clinical efficacy for some indications, but are limited by toxicity and the development of resistance. Their combination with therapeutic vaccines could be a way to improve therapeutic outcome by specifically stimulating the immune system and considering a global approach to tumor microenvironment remodeling.